SARS-CoV-2 Susceptibility and ACE2 Gene Variations Within Diverse Ethnic Backgrounds - Vadgama, Nirmal; Kreymerman, Alexander; Campbell, Jackie; Shamardina, Olga; Brugger, Christiane; Research Consortium, Genomics England; Deaconescu, Alexandra M.; Lee, Richard T.; Penkett, Christopher J.; Gifford, Casey A.; Mercola, Mark; Nasir, Jamal; et al. (Frontiers in Genetics, 2022)
There is considerable variability in the susceptibility and progression for COVID-19 and it appears to be strongly correlated with age, gender, ethnicity and pre-existing health conditions. However, to our knowledge, cohort studies of COVID-19 in clinically vulnerable groups are lacking. Host genetics has also emerged as a major risk factor for COVID-19, and variation in the ACE2 receptor, which facilitates entry of the SARS-CoV-2 virus into the cell, has become a major focus of attention. Thus, we interrogated an ethnically diverse cohort of National Health Service (NHS) patients in the United Kingdom (UK) to assess the association between variants in the ACE2 locus and COVID-19 risk. We analysed whole-genome sequencing (WGS) data of 1,837 cases who were tested positive for SARS-CoV-2, and 37,207 controls who were not tested, from the UK’s 100,000 Genomes Project (100KGP) for the presence of ACE2 coding variants and expression quantitative trait loci (eQTLs). We identified a splice site variant (rs2285666) associated with increased ACE2 expression with an overrepresentation in SARS-CoV-2 positive patients relative to 100KGP controls (p = .015), and in hospitalised European patients relative to outpatients in intra-ethnic comparisons (p = .029). We also compared the prevalence of 288 eQTLs, of which 23 were enriched in SARS-CoV-2 positive patients. The eQTL rs12006793 had the largest effect size (d = 0.91), which decreases ACE2 expression and is more prevalent in controls, thus potentially reducing the risk of COVID-19. We identified three novel nonsynonymous variants predicted to alter ACE2 function, and showed that three variants (p.K26R, p.H378R, p.Y515N) alter receptor affinity for the viral Spike (S) protein. Variant p.N720D, more prevalent in the European population (p < .001), potentially increases viral entry by affecting the ACE2-TMPRSS2 complex. In conclusion, the spectrum of genetic variants in ACE2 may inform risk stratification of COVID-19 patients and could partially explain the differences in disease susceptibility and severity among different ethnic groups.